Transferability and reproducibility of exposed air-liquid interface co-culture lung models - Kirsty Meldrum (NanoImpact, 2023)
Background: The establishment of reliable and robust in vitro models for hazard assessment, a prerequisite for moving away from animal testing, requires the evaluation of model transferability and reproducibility. Lung models that can be exposed via the air, by means of an air-liquid interface (ALI) are promising in vitro models for evaluating the safety of nanomaterials (NMs) after inhalation exposure. We performed an inter-laboratory comparison study to evaluate the transferability and reproducibility of a lung model consisting of the human bronchial cell line Calu-3 as a monoculture and, to increase the physiologic relevance of the model, also as a coculture with macrophages (either derived from the THP-1 monocyte cell line or from human blood monocytes).The lung model was exposed to NMs using the VITROCELL® Cloud12 system at physiologically relevant dose levels.Results: Overall, the results of the 7 participating laboratories are quite similar. After exposing Calu-3 alone and Calu-3 co-cultures with macrophages, no effects of lipopolysaccharide (LPS), quartz (DQ12) or titanium dioxide (TiO2) NM-105 particles on the cell viability and barrier integrity were detected. LPS exposure induced moderate cytokine release in the Calu-3 monoculture, albeit not statistically significant in most labs. In the co-culture models, most laboratories showed that LPS can significantly induce cytokine release (IL-6, IL-8 and TNF-α). The exposure to quartz and TiO2 particles did not induce a statistically significant increase in cytokine release in both cell models probably due to our relatively low deposited doses, which were inspired by in vivo dose levels.The intra- and inter-laboratory comparison study indicated acceptable interlaboratory variation for cell viability/toxicity (WST-1, LDH) and transepithelial electrical resistance, and relatively high inter-laboratory variation for cytokine production.Conclusion: The transferability and reproducibility of a lung co-culture model and its exposure to aerosolized particles at the ALI were evaluated and recommendations were provided for performing inter-laboratory comparison studies. Although the results are promising, optimizations of the lung model (including more sensitive read-outs) and/or selection of higher deposited doses are needed to enhance its predictive value before it may be taken further towards a possible OECD guideline.